Global, regional and national burden of endocrine, metabolic, blood and immune disorders 1990-2019: a systematic analysis of the Global Burden of Disease study 2019 - Wu, Junyun; Lin, Xiling; Huang, Xin; Shen, Yuyan; Shan, Peng-Fei (Frontiers in Endocrinology, 2023)
Background Endocrine, metabolic, blood and immune disorders (EMBID) are a vital public health problem globally, but the study on its burden and global trends is scarce. We aimed to evaluate the global burden of disease and trends in EMBID from 1990 to 2019. Methods We extracted the data of EMBID-related on death cases, Age-standardized death rates (ASDRs), disability-adjusted life-years (DALYs), Age-standardized DALY rates, years of life lost (YLLs), Age-standardized YLL rates, years lived with disability (YLDs) and Age-standardized YLD rates between 1990 and 2019 from the Global Burden of Disease 2019, by sex, age, and year at the global and geographical region levels. The Annual rate of change was directly extracted from Global Health Data Exchange (GHDx) and we also calculated the age-related age-standardized rate (ASR) to quantify trends in EMBID-related deaths, DALYs, YLLs and YLDs. Result Globally, the EMBID-related ASDRs showed an increasing trend, whereas the DALYs ASR, YLLs ASR and YLDs ASR were decreased between 1990 to 2019. Furthermore, High-income North America and Southern Sub-Saharan Africa had the highest both ASDRs and DALYs ASR, and Southern Sub-Saharan Africa and Caribbean had the highest both YLDs ASR and YLLs ASR in 2019. Males had a higher EMBID-related ASDRs than females, but the DALYs ASR in females were higher than males. The burden of EMBID was higher in older-aged compared to other age groups, especially in developed regions. Conclusion Although EMBID-related ASRs for DALYs-, YLLs- and YLDs declined at the global level from 1990 to 2019, but the ASDRs was increasing. This implied high healthcare costs and more burden of ASDRs due to EMBID in the future. Therefore, there was an urgent need to adopt geographic targets, age-specific targets, prevention strategies and treatments for EMBID to reduce negative health outcomes globally.